2013
DOI: 10.1111/nph.12406
|View full text |Cite
|
Sign up to set email alerts
|

Several developmental and morphogenetic factors govern the evolution of stomatal patterning in land plants

Abstract: 598I.599II.601III.601IV.604V.606VI.607VII.608VIII.610611References611 Summary We evaluate stomatal development in terms of its primary morphogenetic factors and place it in a phylogenetic context, including clarification of the contrasting specialist terms that are used by different sets of researchers. The genetic and structural bases for stomatal development are well conserved and increasingly well understood in extant taxa, but many phylogenetically crucial plant lineages are known only from fossils, in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(108 citation statements)
references
References 133 publications
(322 reference statements)
4
103
1
Order By: Relevance
“…S2). The ability of GmSPCH1 to rescue an Arabidopsis spch mutant is consistent with reports that the sequence and function of bHLH transcription factors involved in stomatal formation are highly conserved in land plants (Peterson et al, 2010;MacAlister and Bergmann, 2011;Rudall et al, 2013). Others have shown that a Physcomitrella patens subgroup Ia bHLH transcription factor can partially suppress mute and fama but not spch mutations in Arabidopsis (MacAlister and Bergmann, 2011).…”
Section: Soybean Spch Is Required For Stoma Formation In Embryonic Cosupporting
confidence: 88%
See 1 more Smart Citation
“…S2). The ability of GmSPCH1 to rescue an Arabidopsis spch mutant is consistent with reports that the sequence and function of bHLH transcription factors involved in stomatal formation are highly conserved in land plants (Peterson et al, 2010;MacAlister and Bergmann, 2011;Rudall et al, 2013). Others have shown that a Physcomitrella patens subgroup Ia bHLH transcription factor can partially suppress mute and fama but not spch mutations in Arabidopsis (MacAlister and Bergmann, 2011).…”
Section: Soybean Spch Is Required For Stoma Formation In Embryonic Cosupporting
confidence: 88%
“…Others have shown that a Physcomitrella patens subgroup Ia bHLH transcription factor can partially suppress mute and fama but not spch mutations in Arabidopsis (MacAlister and Bergmann, 2011). Therefore, our results strongly suggest that GmSPCH shares strong functional similarities with Plants exhibit a diversity of stomatal forms, and much of the variation has been attributed to differences in the timing of expression of the subgroup Ia bHLH transcription factors Peterson et al, 2010;Rudall et al, 2013). The extent of stomatal development that occurs during embryogenesis is a reflection of this variability.…”
Section: Soybean Spch Is Required For Stoma Formation In Embryonic Cosupporting
confidence: 52%
“…Studies of fossil stomata and their associated subsidiary and neighboring cells can provide insights into the origin and evolution of developmental pathways of the stomatal complex (Barbacka and Bóka, 2000;Barclay et al, 2007;Bomfleur and Kerp, 2010;Rudall et al, 2013). This is more than just an academic exercise as a deeper understanding of the origin, evolution, and diversity of stomatal developmental pathways in both extant and extinct lineages underpins genetic engineering programs for altered stomatal conductance, assimilation rates, and leaf cooling capacities in modern crop plants.…”
Section: Developmental Insights From the Fossil Stomatal Complexmentioning
confidence: 99%
“…Were paleo-amphistomatous taxa fast growing herbaceous plants or woody shrubs Table I. Stomatal complex types recognized from mature stomata and used in taxonomy and systematics from Cleal and Shute (2012) and Rudall et al (2013) See the Cuticle Database (http://cuticledb.eesi.psu.edu/) and Barclay et al (2007) (Steinthorsdottir et al, 2012), assimilation rate (Brodribb et al, 2007), and water use efficiency from fossilized leaves and cuticle fragments (Franks and Beerling, 2009a;Assouline and Or, 2013;Wilson et al, 2015;McElwain et al, 2016b;Montañez et al, 2016). This opens up the possibility of using stomata to make quantitative paleoecological comparisons between cohabiting fossil taxa (Montañez et al, 2016), which may be more fruitful than grouping all fossil taxa to broadly classify the climatic preference of an entire assemblage or collection locality.…”
Section: Paleoecology and Fossil Stomatamentioning
confidence: 99%
“…Because such data can also be linked to model organism The analysis of phenotypic traits in a phylogenetic framework is key to 5 addressing the evolutionary questions posed by an increasingly diverse set of 6 domains. For example, understanding the evolution of pharyngeal jaw mechanics 7 in fishes (Price et al 2010), identifying phenotype associated genes and 8 regulators in forward genomics approaches (Hiller et al 2012), exploring the 9 key factors in land plant evolution (Rudall et al 2013), or discovering the role 10 of phenotypic traits in colonization ability (Van Bocxlaer et al 2010), all rely on 11 the mapping of phenotypic data to phylogeny. Although robust molecular 12 phylogenies have become easier to generate, more broadly available, and 13 increasingly comprehensive, the phenotypic data on which these studies rely 14 have not.…”
mentioning
confidence: 99%